Developing an interactive folktale-based digital learning application integrating the SQ4R strategy to enhance elementary students’ reading comprehension and narrative writing - N. Yuniar Rizki Siti Amalia; Angga Hadiapurwa; Rina Heryani (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Elementary students frequently encounter difficulties in reading comprehension and narrative writing due to the limited availability of interactive digital learning resources that integrate structured literacy strategies with culturally relevant content. Aims: This study aimed to develop an interactive folktale-based digital learning application integrating the SQ4R (Survey, Question, Read, Recite, Record, and Review) strategy and to evaluate its feasibility and effectiveness in enhancing fourth-grade students’ reading comprehension and narrative writing. Method: A Design and Development approach employing the ADDIE model was adopted. The application was implemented with fourth-grade students from five elementary schools in Sumedang Regency, Indonesia, through one limited trial and four broader field trials. Data were collected using expert validation sheets, reading comprehension and narrative writing tests, and teacher and student response questionnaires. Data were analyzed using the Shapiro–Wilk test, paired-sample t-test or Wilcoxon signed-rank test, and normalized gain (N-Gain). Results: The application achieved a very feasible rating across the material, language, and media aspects. Reading comprehension demonstrated moderate improvement with N-Gain values ranging from 0.51 to 0.55, while narrative writing achieved N-Gain values between 0.48 and 0.55. Significant improvements (p < 0.001) were consistently observed across all participating schools. In addition, both teachers and students provided highly positive evaluations regarding the usability, attractiveness, and instructional value of the application. Conclusion: The developed application provides an effective technology-enhanced literacy learning environment by integrating local folktales with the SQ4R strategy to simultaneously improve reading comprehension and narrative writing. These findings demonstrate the potential of culturally responsive digital learning to support meaningful and integrated literacy instruction in elementary education.